Pengaruh Iklan Televisi dan Word of Mouth (WOM) terhadap Minat Beli Smartphone Mito pada Mahasiswa Universitas Negeri Padang - Septrizola, Whyosi; Rahmiati, Rahmiati; Asria, Maya (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2017)
This research aims to analyze the effects of Television Advertising AndWord of Mouth (WOM) Toward Purchase Intention MiTO Smartphone on Padang State University’s Students. Populations in the research are theall students of students at Padang State University as much as 7.185 persons.Sampling has been developed throughthe accidentall sampling with Cochran, resulting in 300 respondents. The data have been collected by main instrument of questionnaire. Technical data analysis with multiple linear regression and using t-test. The results of research indicate that television advertising and Word of Mouth (WOM) has a significan efect Toward Purchase Intention MiTO Smartphone on Padang State University’s Students.